Tinjauan Kuat Tarik Belah Beton Menggunakan Bahan Substitusi Serat Roving dan Cangkang Tiram - Bunyamin; Heru Pramanda; Munirul Hady; Febrina Dian Kurniasari; Muhammad Anshar (Jurnal Serambi Engineering, 2024)
Additives such as fibres have been widely used to increase the tensile strength of concrete. Previous research has shown that the tensile strength of concrete may also be increased by replacing 10% of the cement with waste materials, such as oyster shell ash. In this research, waste material in the form of oyster shells was combined with roving fibre (gypsum fibre). The objective in this research is to ensure the split tensile strength of concrete using 10% oyster shell waste combined with 5%, 10% and 15% gypsum fibre in cement. The oyster shell waste was sourced from Krueng Neng, Aceh Besar. Gypsum fibre was sourced from a building materials shop in Banda Aceh City. This research used the method of ACI 211.1-91 or American Concrete Institute and ASTM or American Society for Testing and Materials, with cylindrical test specimens (15 cm x 30 cm). The test results showed that the normal splitting tensile strength of concrete was 2.95 MPa. Meanwhile, the splitting tensile strengths of concrete with gypsum fibre and oyster shell ashsubstitution were 3.10 MPa, 3.49 MPa and 3.51 MPa. The combination of oyster shell ash and gypsum fibre in concrete can significantly increase the splitting tensile strength of concrete.